The Eulogy of Urbanity : a critical perspective intersecting urban planning and philosophy - Pereira, Paula Cristina (2011)
The development of cities has led to an ambivalent discourse that has none too often drawn its boundaries from the very delimitation of urban physical space. However, in view of the revitalization of community life, other dimensions, such as the political, social, architectural and urban heritages, should be considered as well. Furthermore, the contemporary city with its multicultural character requires a renewed urbanity of thought. With this in mind, this paper proposes an approach that goes beyond a strictly utilitarian understanding of the city, by intersecting insights from architecture, urbanism and philosophy. It is intended to provoke and to inform new urban policies and their management models, with a view to achieving true civility, and to highlight what unites these spheres of knowledge rather than what separates them.